2017
DOI: 10.1063/1.4974280
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of spin orbit torques in a Tb-Co alloy magnetic wire by controlling its Tb composition

Abstract: We investigated the current-induced domain wall motion (CIDWM) in Pt(3 nm)/TbxCo1-x(6 nm) alloy wires with various Tb composition (x). We found that the threshold current density (Jth) for the CIDWM in the TbxCo1-x alloy wires decreases with increasing x. In particular, the Jth with x = 0.37 is almost 3 times smaller than that with x = 0.23. We estimated Dzyaloshinskii-Moriya interaction (DMI) effective field (HDMI) by measuring CIDWM in a longitudinal magnetic field. We found that DMI constant (D) estimated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…The same order of magnitude of velocity for CoTb was observed by Kurokawa et al . 46 Here, the gap between the DW velocities is probably caused by the different magnetic anisotropy. Compared to the Gd-based alloys, larger magnetic anisotropy constant ( K u ) values have been reported in Tb-based alloys, 42,45,47,48 which is induced by the single-ion anisotropy contribution from Tb.…”
Section: Resultsmentioning
confidence: 92%
“…The same order of magnitude of velocity for CoTb was observed by Kurokawa et al . 46 Here, the gap between the DW velocities is probably caused by the different magnetic anisotropy. Compared to the Gd-based alloys, larger magnetic anisotropy constant ( K u ) values have been reported in Tb-based alloys, 42,45,47,48 which is induced by the single-ion anisotropy contribution from Tb.…”
Section: Resultsmentioning
confidence: 92%
“…Оскільки, попри те, що вплив розмірних ефектів на фізичні властивості тонкоплівкових магнетиків, в основі яких рідкоземельні та феромагнетні метали, детально вивчено у багатьох роботах (див., наприклад, [13][14][15]), інформація про особливості кристалічної структури, фазового складу, електрофізичних та магнеторезистивних властивостей плівкових систем на основі Dy у поєднанні з Со або Ni обмежена. Тому основний акцент наших досліджень спрямовано на вивчення розмірних та концентраційних ефектів у структурно-фазовому стані, електро-та магнетотранспортних властивостей функціональної системи Ni/Dy/Co в умовах фазоутворення у процесі конденсації зразків та дифузії під впливом температурної обробки.…”
Section: вступunclassified
“…[4][5][6][7][8][9][10][11] In previous studies, we reported that perpendicular magnetized rare-earth magnetic wires also have low J th for CIDWM. The J th values of rare-earth magnetic wires, for example Tb/Co, 8 TbFeCo, 12,13 GdFeCo, 14 and Tb-Co wires, 15 are much lower than those of in-plane magnetized wires such as FeNi. 16 Recently, the contributions of the spin hall effect (SHE) and Dzyaloshinskii-Moriya interaction (DMI), which are generated at heavy metal/ferromagnetic layer interfaces, to CIDWM have been reported.…”
mentioning
confidence: 92%
“…16 Recently, the contributions of the spin hall effect (SHE) and Dzyaloshinskii-Moriya interaction (DMI), which are generated at heavy metal/ferromagnetic layer interfaces, to CIDWM have been reported. 15,[17][18][19][20][21][22][23][24][25][26][27][28] SHE and DMI induced torques are more effective for CIDWM than conventional spin transfer torques. For example, the DW velocity in perpendicular magnetized magnetic wires with heavy metal layers is much faster than that in magnetic wires without such layers.…”
mentioning
confidence: 99%